Development of vibration suppression devices from smart fluids - Rashid, Muhammad Mahbubur; Salami, Momoh Jimoh Emiyoka; Khan, Md. Raisuddin; Rahman, Md. Mozasser (Trans Tech Publications, Switzerland, 2011)
Semi-active control devices have received significant attention in recent years because they offer the adaptability of active control devices without requiring the associated large power sources. Magneto-rheological (MR) dampers are semi-active control devices that use MR fluids to produce controllable dampers. They potentially offer highly reliable operation and can be viewed as fail-safe in that they become passive dampers should the control hardware malfunction. To develop control algorithms that take maximum advantage of the unique features of the MR damper, models must be developed that can adequately characterize the damper 19s intrinsic nonlinear behavior. Following a review of several idealized mechanical models for controllable fluid dampers, a model is proposed that can effectively portray the behavior of a typical magneto-rheological damper. Comparison with experimental results for a prototype damper indicates that the model is accurate over a wide range of operating conditions and is adequate for control design and analysis.